Răspuns :
Răspuns:
Explicație pas cu pas:
a + b = 1 285
a : b = 6 rest 4 ⇒ a = 6 × b + 4
(6 × b + 4) + b = 1 285
7 × b = 1 285 - 4
7 × b = 1 281
b = 1 281 : 7 ⇒ b = 183
a = 1 285 - 183 ⇒ a = 1 098
A + B = 1.285
A : B = 6 rest 4
A = 6 × B + 4
6 × B + 4 + B = 1.285
7 × B + 4 = 1.285
7 × B = 1.285 - 4
7 × B = 1.281
B = 1.281 : 7
B = 183
A = 6 × 183 + 4
A = 1.098 + 4
A = 1.102
A : B = 6 rest 4
A = 6 × B + 4
6 × B + 4 + B = 1.285
7 × B + 4 = 1.285
7 × B = 1.285 - 4
7 × B = 1.281
B = 1.281 : 7
B = 183
A = 6 × 183 + 4
A = 1.098 + 4
A = 1.102